2009
DOI: 10.1111/j.1474-919x.2009.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematozoa infections in a Great TitParus majorpopulation in Central Portugal: relationships with breeding effort and health

Abstract: Blood parasites may act as modulators of their hosts' ecology, life histories and fitness. We studied the prevalence of Plasmodium sp., Haemoproteus sp. and Leucocytozoon sp. and their effects on morphological, biochemical and haematological variables and on breeding effort of Great Tits Parus major. Total prevalence (percentage of individuals infected by any parasite) ranged from 7.7% to 61.1%. There was an overall positive association in prevalence between the three haematozoan parasites. No effect of sex or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 70 publications
10
48
2
3
Order By: Relevance
“…Similarly, infection status could be influenced by sex, with males experiencing higher susceptibility to parasites, possibly as a result of the energetic trade-off between immunocompetence and reproductive effort (Norris et al 1994;Richner et al 1995;Zuk and McKean 1996). Norte et al (2009) suggested that females experience more costly energetic constraints on immune function during the incubation period, while males experience depressed immune function during the brood-rearing period. Such partitioning of reproductive investment could influence the appearance of malaria infections in the circulating blood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, infection status could be influenced by sex, with males experiencing higher susceptibility to parasites, possibly as a result of the energetic trade-off between immunocompetence and reproductive effort (Norris et al 1994;Richner et al 1995;Zuk and McKean 1996). Norte et al (2009) suggested that females experience more costly energetic constraints on immune function during the incubation period, while males experience depressed immune function during the brood-rearing period. Such partitioning of reproductive investment could influence the appearance of malaria infections in the circulating blood.…”
Section: Introductionmentioning
confidence: 99%
“…Such partitioning of reproductive investment could influence the appearance of malaria infections in the circulating blood. Infection status may also be influenced by body condition, with infection or failure to control infection more likely among birds in poorer condition (Dawson and Bortolotti 2000;Norte et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Haemosporidian prevalence usually increases in spring in temperate regions (Hatchwell et al 2000;Norte et al 2009), and an autumn peak may also be observed (Cosgrove et al 2008). In this study, we found that haemosporidian prevalence had a different pattern, being lower in spring, intermediate in autumn and higher in winter.…”
Section: Discussionmentioning
confidence: 54%
“…The increase of glutathione peroxidase activity may be one protective action to recover from the potential unbalance in oxidative status (Meister and Anderson, 1983). Our previous study, in a nearby mixed deciduous woodland, also showed that both Plasmodium and Leucocytozoon infected great tits had significantly higher glutathione peroxidase activity (Norte et al 2009). Isaksson et al (2013) also reported that the levels of total and oxidized glutathione in great tits were significantly affected by the Plasmodium infection status, which could be related with the activity of glutathione peroxidase (Meister and Anderson, 1983).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation